HUBUNGAN KESUBURAN TANAH DENGAN PRODUKTIVITAS TANAMAN - Asmar Asmar; Amrizal Saidi; Masliyunas Masliyunas (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
A research about relationship between soil properties and crop yield was conducted in Pandai Sikek, Tanah Datar Region, center for cabbage and carrot production, West Sumatra in 2004 and 2005. Soil samples were collected from rainfed paddy soils by purposive random sampling. Soil samples were analyzed in Soil Laboratory, Agriculture Faculty and Agriculture Polytechnique Laboratory, Andalas University. Several soil physical properties analysed were soil bulk density and total soil pores by using gravimetric method, permeability with de Boodt method, soil water content at several pF values using pressure plate apparatus, and soil strength by using penetrometer. Soil chemical parameters analysed were soil pH using pH-meter, organic-C using Walkley and Black, available P using Bray II, and cation exchange capacity using NH4-leaching at pH 7.0, and N-total using Kjehdhal method. Crop productions were sampled from a 3x3 m2 of soil sampling area. The result showed that soils planted by cabbage and carrot had good soil physical properties, such as having balanced pore size distribution. The chemical properties of the soils were good as well, except N, K- and Ca-exchangeable which were very low. The other soil properties were quite good. Soil physical properties gave different response on both crops. Carrots were more response aeration pore and soil organic matter content, then cabbage was more response on BV, TSP, and slow drainage pores. While soil chemical properties did not give significant response. Both crops responded on Ca, but cabbage was more response on N-total, and carrot on CEC and saturated cationKey Words: Soil Physical Properties, Soil Fertility, Crop Productivity